Measuring the endangering stage of indigenous Gayonese language and its relation to English as a global language - Munandar, Imam (Englisia: Journal of Language, Education, and Humanities, 2023)
There has been a growing concern about the decreasing number of the Gayonese young generation who are literate in their mother language. Unfortunately, little scientific effort has been made to determine its leading causes. While the previous studies limitedly focused on the structure and form of the Gayonese language, this research seeks to fill the gap by attempting to uncover the contributing factors leading to the Gayonese young adults' reluctance to employ the Gayonese language in their regular interaction and their views regarding the language. Besides, the study attempts to determine if English as a global language has to do with endangering the Gayo language. The research employed a case study methodology and semi-structured interviews to collect data. The data is mined from thirty university students, aged 18-21 years old, who have Gayonese language background. The result of the research showed that unfavorable views against the Gayonese language are on the rise among the young Gayonese generation. Furthermore, young Gayonese are now used to speaking the official Indonesian language instead of their native tongue for the following reasons; the Indonesian language indicates upper-class status and is more prestigious; the Indonesian language is more sensible and efficient for talking with the opposite sex; and the Indonesian language is more straightforward and more accessible to use when greeting new friends. Meanwhile, it is also revealed that the powerful status of English as a global language has nothing to do with the cause of the young Gayonese generation abandoning their mother tongue. Given this finding, the researcher envisages the Gayonese language as in stage six of the endangered language according to the GIDS scale. Stage six suggests that the language needs preservative treatments to avoid a total loss. The researcher also forwards that the Gayonese families introduce the mother language to their children at an early age and better realize that English is not the cause of abandoning the Gayonese language by their children. Also, the local government should carry out language revitalizing efforts by regulating the provision of the Gayonese language in primary schools.